INCORPORATING GOOD GOVERNANCE IN - TANDA, SISA (My University, 2011)
CPA’s and LED have been used as a means of alleviating poverty in most countries and South Africa is no exception. However, in order for the CPAs and or LED to function properly incorporating good governance in these government initiatives is key long term sustainability. The study begins by exploring global trends on LED, thereafter looks at LED initiatives and strategy of the country. The study then concentrates in Mpumalanga Province and thereafter looks at Dwaleni Community where the focus for this study is. The aim of the study is to explore successes and challenges of the current CPA and LED in South Africa and how to incorporate good governance as a means of accelerating poverty alleviation. Based on the literature review, interviews, data collection and analysis, the researcher found some challenges. The researcher also highlighted that the study could be of benefit to Policy Makers, Government Department Official, Community and other interested stakeholders who have interests in promoting Public & Economic Development. The findings from this research could be useful in forming the basis for further research
MM - P&DM
Keywords: Economic development; Governance; Property